National Trends in Antibiotic Use in Australian Residential Aged Care Facilities, 2005–2016. (27th May 2020) - Sluggett, Janet K; Moldovan, Max; Lynn, David J; Papanicolas, Lito E; Crotty, Maria; Whitehead, Craig; Wesselingh, Steve L; Rogers, Geraint B; Inacio, Maria C
Abstract: Background: Understanding current patterns of antibiotic use in residential aged care facilities (RACFs) is essential to inform stewardship activities, but limited utilization data exist. This study examined changes in prevalence and consumption of antibiotics in Australian RACFs between 2005–2006 and 2015–2016. Methods: This population-based, repeated cross-sectional analysis included all long-term permanent residents of Australian RACFs between July 2005 and June 2016 who were aged ≥ 65 years. The yearly prevalence rate of antibiotic use and number of defined daily doses (DDDs) of systemic antibiotics per 1000 resident-days were determined annually from linked pharmaceutical claims data. Trends were assessed using ordinary least squares regression. Results: This study included 502 752 residents from 3218 RACFs, with 424.9 million resident-days analyzed. Antibiotics were dispensed on 5 608 126 occasions during the study period, of which 88% were for oral use. Cefalexin, amoxicillin-clavulanic acid, and trimethoprim were the most commonly dispensed antibiotics. The annual prevalence of antibiotic use increased from 63.8% (95% confidence interval [CI], 63.3%–64.4%) to 70.3% (95% CI, 69.9%–70.7%) between 2005–2006 and 2015–2016 (0.8% average annual increase, P < .001). There was a 39% relative increase in total consumption of systemic antibiotics, with utilization increasing from 67.6 to 93.8 DDDs/1000 resident-days during the study period (average annual increase of 2.8 DDDs/1000 resident-days, P < .001). Conclusions: This nationwide study showed substantial increases in both prevalence of use and total consumption of antibiotics in Australian RACFs between 2005 and 2016. The increasingly widespread use of antibiotics in Australian RACFs is concerning and points to a need for enhanced efforts to optimize antibiotic use in this setting.